2018
DOI: 10.14507/epaa.26.3563
|View full text |Cite
|
Sign up to set email alerts
|

Forbes 30 under 30 in education: Manufacturing “edu-preneur” networks to promote and reinforce privatization/marketization in education

Abstract: Each year Forbes bestows a handful of “edu-preneurs” with the 30 Under 30 Award in Education (Under30), designating those individuals as the best hope for revolutionizing and reforming education. Boasting low recipient rates, Forbes elevates the manufactured expertise of awardees and the importance of their organizations and ventures. Further, Forbes employs the language and norms of neoliberalism to articulate a pro-market vision of education reform. This social network analytic (SNA) study seeks to untangle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…This finding underscored previous research from Kretchmar et al (2014) that utilized a policy network analysis, to create a visual representation of TFA’s key role in developing and connecting personnel, political support, and financial backing to create a powerful network of interdependent organizations and individuals who promote and implement the expansion of charter schools and other market-based reforms. Brewer et al (2018) also found that TFA alumni networks and donors have been a primary ideological and political driving force for privatization and private control of public schools.…”
Section: Discussionmentioning
confidence: 96%
“…This finding underscored previous research from Kretchmar et al (2014) that utilized a policy network analysis, to create a visual representation of TFA’s key role in developing and connecting personnel, political support, and financial backing to create a powerful network of interdependent organizations and individuals who promote and implement the expansion of charter schools and other market-based reforms. Brewer et al (2018) also found that TFA alumni networks and donors have been a primary ideological and political driving force for privatization and private control of public schools.…”
Section: Discussionmentioning
confidence: 96%
“…The organization continues to hold a powerful seat at the education policy table (Alter, 2011; Clark, Isenberg, Liu, Makowsky, & Zukiewicz, 2015; Mead, 2015). Yet a growing body of literature continues to call into question TFA’s recruitment, training, and relying on individual narratives of triumph and “saviorism” to sustain an influx of recruits, donors, and positive public support (Brewer, 2014; Brewer, Hartlep, & Scott, 2018; White, 2015; Waldman, 2019).…”
Section: Introductionmentioning
confidence: 99%